(untitled) (International Journal of Engineering and Computer Science, 2015)
This work proposes a steganalysis scheme based on Hopping cluster algorithm. The proposed scheme focuses on detection of the steganography algorithm used rather than detection of hidden message only. Even hidden message can also be detected using this alogorithm. Experimental results shows that message can also be detected but if once steganography algorithm is detected all the images steganographed can be detected very easily so this algorithm is quite effective than previous algorithms.